From Resources to Performance: Job Satisfaction as a Conversion Mechanism for Knowledge Management, Work Culture, and Intellectual Integrity in Hotels - Yandra Rivaldo; Andika Prasetya Nugraha; Robby Kurniawan; Tantri Widriati (Advances in Human Resource Management Research, 2025)
Purpose: This study examines how knowledge management, work culture, and intellectual integrity are translated into employee performance through job satisfaction in the hotel sector, with a focus on high-contact service environments. Research Method: An explanatory survey reached 235 permanent employees of three-star hotels in Batam, Indonesia, sampled proportionately from a frame of 566. All five constructs were modelled as second-order latent variables in LISREL 8.70. Results and Discussion: The results indicate that knowledge management, work culture, and intellectual integrity are positively associated with job satisfaction. In turn, job satisfaction demonstrates a strong relationship with employee performance. The model explains 57% of the variance in job satisfaction and 86% of the variance in employee performance. Indirect effects show consistent partial mediation, indicating that job satisfaction functions as a central mechanism through which organisational resources are translated into performance outcomes. Implications: Job satisfaction warrants managerial attention as the mechanism linking resource investment to employee performance, not as a by-product of human resource practice. Existing studies have largely examined knowledge management, work culture, and ethical constructs in isolation, with limited explanation of how these heterogeneous resources are jointly translated into performance. This study addresses this gap by proposing a unified conversion-based framework centred on job satisfaction as a common mechanism. It further positions intellectual integrity as a distinct individual-level epistemic resource, extending established ethical perspectives in hospitality research.